Answer:
(-4,-9)
Step-by-step explanation:
Given a segment AB with endpoints with coordinates
A: [tex](x_A,y_A)[/tex]
B: [tex](x_B,y_B)[/tex]
The coordinates of the midpoint M of the segment AB are given by:
[tex]x_M = x_A + \frac{x_B-x_A}{2}\\y_M = y_A + \frac{y_B-y_A}{2}[/tex] (1)
In this problem, we know that:
- The midpoint of the segment AB has coordinates
[tex]x_M=2\\y_M=-7[/tex]
- One of the endpoint of the segment has coordinates
[tex]x_B=8\\y_B=-5[/tex]
So we can find the coordinates of the other endpoint A by re-arranging eq.(1) above:
[tex]x_A=2x_M-x_B\\y_A=2y_M-y_B[/tex]
And substituting, we find:
[tex]x_A=2(2)-8=-4\\y_A=2(-7)-(-5)=-9[/tex]
So, the coordinates of the other endpoint are (-4,-9).